2003
DOI: 10.1093/annonc/mdg170
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine and oxaliplatin for metastatic pancreatic adenocarcinoma: a North Central Cancer Treatment Groupphase II study

Abstract: Gemcitabine and oxaliplatin, at doses of 1000 mg/m(2) and 100 mg/m(2), respectively, showed moderate activity in patients with pancreatic ACA. Based on the results of this study further evaluation of this combination is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 14 publications
2
18
1
2
Order By: Relevance
“…The grade 3/4 thrombocytopenia rate of 70% reported in our study was substantially higher than that reported by other authors, with a reported range from 9 to 24% [11,17,18,19,20]. One possible explanation for this discrepancy is the higher dose of oxaliplatin used in our study, and another may be the heterogeneity of the cohorts in the different studies.…”
Section: Discussioncontrasting
confidence: 86%
“…The grade 3/4 thrombocytopenia rate of 70% reported in our study was substantially higher than that reported by other authors, with a reported range from 9 to 24% [11,17,18,19,20]. One possible explanation for this discrepancy is the higher dose of oxaliplatin used in our study, and another may be the heterogeneity of the cohorts in the different studies.…”
Section: Discussioncontrasting
confidence: 86%
“…Encouraging results were obtained in some phase II trials using different schedules with an overall TTP from 3.6 to 5.7 and an OS from 5.6 to 9.5 months (37)(38)(39)(40)(41)(42)(43)(44)47). In particular, a preliminary trial assessed the combination of gemcitabine (1000 mg/m 2 as a 10 mg/m 2 /min infusion on day 1) plus oxaliplatin (100 mg/m 2 as a 2-h infusion on day 2 every two Table II.…”
Section: Gemcitabine and Capecitabinementioning
confidence: 95%
“…Oxaliplatin-based regimen mostly used for treatment of metastatic colorectal and pancreatic cancers with promising results [17]- [20]. In our department, many regimens of chemotherapy were used to treat metastatic cervical cancer.…”
Section: Discussionmentioning
confidence: 99%